Enhancing Students’ English Public Speaking Skills through Debate Technique - Palupi, Muji Endah; Nurdini, Rahmi Aulia; Sulistyawati, Meiva Eka Sri; Andayani, Endang Sri (British (Jurnal Bahasa dan Sastra Inggris), 2025)
This study examines the impact of the debate technique on improving English public speaking skills among college students learning English as a foreign language. Conducting a Classroom Action Research (CAR) with 38 participants over 12 weeks, the researchers identified initial deficiencies in speaking abilities such as vocabulary, pronunciation, and fluency, highlighted by students' anxiety and low confidence. The intervention, implemented in two cycles, utilized British Parliamentary debate formats to develop critical thinking, argumentation, and public speaking proficiency. Results demonstrated substantial enhancement, increasing from 44.74% to 94.74% in students meeting required competency benchmarks, specifically being able to master public speaking with scores exceeding the passing grade. The findings affirm that debate techniques significantly foster confidence, fluency, and overall speaking abilities. This research highlights the importance of dynamic teaching methods in developing effective communicators in a globalized context. Keywords: Public Speaking; Debate; Classroom Action Research